Long term outcomes of occipital nerve stimulation - Montenegro, Monique M.; Kissoon, Narayan R. (Frontiers in Pain Research, 2023)
Background: Occipital nerve stimulation has been investigated as a potential treatment for disabling headaches and has shown promise for disorders such as chronic migraine and cluster headache. Long term outcomes stratified by headache subtype have had limited exploration, and literature on outcomes of this neuromodulatory intervention spanning 2 or more years is scarce. Measures: We performed a narrative review on long term outcomes with occipital nerve stimulation for treatment of headache disorders. We surveyed the available literature for studies that have outcomes for 24 months or greater to see if there is a habituation in response over time. Review of the literature revealed limited evidence for occipital neuralgia, chronic migraine, cluster headache, and cervicogenic headache. While the term ‘response’ varied per individual study, a total of 12 studies showed outcomes in occipital nerve stimulation with long term sustained responses (as defined per study) in the majority of patients with specific head types 153/256 (60%). There was a paucity of studies that provided both short term and long term responses to occipital nerve stimulation with 4 studies in total (3 cluster and 1 cervicogenic headache). In the cluster headache cumulative population, the majority of patients (64%) were long term responders (as defined per study) and only a minority of patients 12/62 (19%) had loss of efficacy (e.g., habituation). There was a high number 280/366 (77%) of adverse events per total number of patients in the studies including lead migration, requirements of revision surgery, allergy to surgical materials, infection and intolerable paresthesias. Conclusions: With the limited evidence available, the response to occipital nerve stimulation was sustained in the majority of patients with cluster headache with low rates of loss of efficacy in this patient population. There was a high percent of adverse events per number of patients in long term follow-up and likely related to the off-label use of leads typically used for spinal cord stimulation. Further longitudinal assessments of outcomes in occipital nerve stimulation with devices labelled for use in peripheral nerve stimulation are needed to evaluate the extent of habituation to treatment in headache.